Composite cathode material, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202611065764.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-17
AI Technical Summary
然而,将无序岩盐锰酸锂与富锂磷酸铁锂相结合,特别是构建明确的核壳结构,仍面临挑战:两者晶格常数差异大(失配度可达10%),难以通过常规方法实现稳固结合
1、本发明的复合正极材料的内核基体包括无序岩盐-尖晶石锰酸锂,其作用承担主要的锂存储任务,贡献最高的可逆容量和平均放电电压。无序岩盐结构可降低阳离子的长程有序性,进而使材料有更高的容量。尖晶石结构因其固有O-TM四面体提供低能垒的三维锂离子扩散通道,有利于提高其倍率性能。此外,尖晶石结构能够部分保证结构的相对稳定性。
Smart Images

Figure CN122619775B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode material technology, and in particular to a composite cathode material, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are the electrochemical energy storage system with high energy density and the best overall performance. Improving energy density is the main goal of lithium battery research and development. China, the United States, Japan, South Korea, Europe, and other countries have all included the development of 400-600Wh / kg lithium batteries in their medium- to long-term plans for lithium battery development. Improving the performance of cathode materials (such as capacity, operating voltage, and structural stability) is the core approach to improving battery energy density.
[0003] Currently, commercially available cathode materials (such as lithium cobalt oxide and ternary materials) are limited by the cost and supply chain issues of scarce metals such as cobalt and nickel. Lithium-rich disordered rock salt cathode materials (such as disordered rock salt lithium manganese oxide) prepared using low-cost and environmentally friendly metals have become a research hotspot due to their high specific capacity and high operating voltage; however, their inherent poor cycle stability (oxygen release, structural degradation, and severe voltage decay during charge and discharge) restricts their commercial application. On the other hand, lithium iron phosphate (LFP) and its lithium-rich derivatives are known for their ultra-high structural stability and cycle life, but their operating voltage and theoretical capacity are relatively low.
[0004] A single material cannot simultaneously meet the requirements of high capacity, high stability, and high rate performance. In recent years, researchers have attempted to combine different cathode materials to leverage their respective strengths and compensate for their weaknesses. For example, some researchers have used high-energy ball milling to combine polyanionic materials (such as PO4)... 3- Introducing a lithium-rich rock salt structure effectively stabilizes lattice oxygen and improves the material's cycling performance. Other studies have also achieved good results by constructing core-shell structures and coating high-capacity materials with stable materials. However, combining disordered rock salt lithium manganese oxide with lithium-rich lithium iron phosphate, especially constructing a defined core-shell structure, still faces challenges: the large difference in lattice constants between the two (mismatch can reach 10%) makes it difficult to achieve a stable bond using conventional methods. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a composite cathode material, its preparation method, and a lithium-ion battery. This composite cathode material, through the construction of a unique core-shell structure, combines the high capacity, high voltage, and high rate capability of lithium manganese oxide with the high stability of lithium iron phosphate, achieving synergistic enhancement. Ultimately, it yields a high-energy-density lithium-ion battery cathode material with excellent overall performance. Lithium-ion batteries prepared using this composite cathode material exhibit approximately 30% higher capacity retention after 500 cycles at 1C.
[0006] The objective of this invention is achieved through the following technical solution: a composite cathode material having a core-shell structure; the core-shell structure comprising, from the inside out, a core matrix, a transition layer, and an outer shell; the core matrix being disordered rock salt-spinel lithium manganese oxide; the transition layer being lithium manganese oxide; and the outer shell being lithium iron phosphate rich in lithium; The composite cathode material has the following characteristics: (1) The general chemical formula of the disordered rock salt-spinel lithium manganese oxide core matrix is: Li 1+b Mn 0.8-y N y O 2-y F n ;in, 0.1 < b ≤ 0.3, 0.1 < y ≤ 0.5, 0.05 < n ≤ 0.2; N is Mg 2+ Fe 3+ Ti 4+ Zr 4+ 、Nb 5+ Mo 6+ Ta 5 + W 6+ One or more of the following; (2) The transition layer lithium manganese oxide has a spinel structure and its chemical formula is: LiMn2O4; (3) The general chemical formula of the lithium iron phosphate shell is: Li 1+a Fe 1-x M x PO4; where 0 < a ≤ 0.2, 0 ≤ x ≤ 0.2; M is Mg 2+ Ti 4+ Zr 4+ Mn 2+ Zn 2+ Cu 2+ Al 3+ V 3+ Cr 3+ Co 2+ Ni 2+ One or more of the following; The core matrix has a particle size of 200nm to 500nm; the transition layer has a thickness of 5nm to 50nm; and the outer shell has a thickness of 10nm to 100nm.
[0007] The present invention also provides a method for preparing a composite cathode material, which includes the following steps: Step 1: Preparation of the core matrix: According to the stated chemical formula Li 1+b Mn 0.8-y N y O2-y F n Manganese source, lithium source, N metal source and lithium fluoride were weighed according to the stoichiometric ratio, dissolved in solvent, ball-milled and mixed evenly, and dried to obtain the first precursor powder; the first precursor powder was pressed into tablets and sintered in two stages under a protective atmosphere. The sintered material was quickly taken out from the high-temperature furnace and put into the cooling medium. After refining, the disordered rock salt-spinel lithium manganese oxide core matrix was obtained. Step 2: Constructing the transition layer: The disordered rock salt-spinel lithium manganese oxide core matrix obtained in Step 1 is dispersed in a solvent, and lithium acetate and manganese acetate are added, wherein the lithium-manganese molar ratio is Li:Mn = (1.0~1.10): 2; stirring and evaporation are carried out to coat the disordered rock salt-spinel lithium manganese oxide core matrix with the lithium manganese oxide precursor; after drying, it is sintered in an oxygen atmosphere to form an intermediate product with a lithium manganese oxide transition layer; the optimal lithium-manganese molar ratio is Li:Mn = (1.02~1.05): 2; a slight excess of lithium can compensate for lithium volatilization during the sintering process; an excess will generate an inert phase, affecting the capacity; Step 3: Preparation of composite cathode material: The intermediate product obtained in Step 2 is dispersed in a solvent to obtain solution A; according to the stated chemical formula Li 1+a Fe 1-x M x Iron, phosphorus, lithium, M metal, and carbon sources were weighed out according to the stoichiometric ratio of PO4, and solvent and dispersant were added. The mixture was ball-milled to obtain solution B. Under the combined action of stirring and sonication, solution B was slowly added dropwise to solution A. The mixture was stirred and evaporated, so that solution B was uniformly nucleated and precipitated on the surface of the intermediate product to obtain a slurry. The slurry was dried to obtain a second precursor powder, which was then pressed into tablets, sintered under a protective atmosphere, and pulverized by airflow to obtain a composite cathode material. In step one, the manganese source is selected from one or more of manganese dioxide, manganese nitrate, and manganese chloride; the lithium source is selected from one or more of lithium hydroxide, lithium nitrate, and lithium carbonate; in step three, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium acetate; the iron source is selected from one or more of ferrous oxalate, ferric phosphate, and ferrous chloride; the phosphorus source is selected from one or more of monoammonium phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate; in step three, the carbon source is selected from one or a combination of two of glucose, sucrose, citric acid, ascorbic acid, tartaric acid, polyethylene glycol, polyvinyl butyral, polyvinyl alcohol, and starch, with the carbon source content accounting for approximately 3wt% to 15wt% of the total solids; in step three, the dispersant is selected from one of polyethylene glycol, ethylene glycol, polyacrylic acid, and stearic acid; in steps one and three, the protective atmosphere during sintering is one of nitrogen, argon, and helium; the solvent used in steps one, two, and three is anhydrous ethanol. Step one, specifically the two-stage sintering process, includes the following steps: The first stage adopts low-temperature sintering: heating rate 5℃ / min~15℃ / min; sintering temperature 800℃~1000℃; sintering time 8h~12h. The second stage uses high-temperature sintering: the heating rate is 2℃ / min~5℃ / min; the sintering temperature is 1100℃~1300℃; the sintering time is 8h~12h; in step one, the cooling medium used after the two stages of sintering is liquid nitrogen or ice water. In step one, the ball mill speed is 300 rpm to 500 rpm; the ball milling time is 5 h to 8 h; in step three, the ball mill speed is 600 rpm to 800 rpm; the ball milling time is 2 h to 5 h. In step three, the ultrasonic frequency is 120 kHz to 180 kHz; the stirring speed is 200 rpm to 400 rpm; the solution dropping rate is 5 ml / min to 50 ml / min; in step three, the heating rate during sintering is 2℃ / min to 5℃ / min, the sintering temperature is 600℃ to 850℃, and the sintering time is 8h to 12h. In steps one, two, and three, the drying temperature is 75℃~120℃, and the drying time is 6h~12h; in steps one and three, the drying powder is pressed into flakes under conditions of 15 MPa~25 MPa; in steps two and three, the solution is stirred and evaporated at a temperature of 45℃~80℃.
[0008] The present invention also provides a lithium-ion battery, comprising: a positive current collector, a negative current collector, a separator, and an electrolyte solution; wherein the positive current collector is coated with a positive electrode layer; the positive electrode layer comprises a positive electrode material; the positive electrode material is the aforementioned composite positive electrode material. The present invention has the following advantages: 1. The core matrix of the composite cathode material of the present invention comprises disordered rock salt-spinel lithium manganese oxide, which undertakes the main lithium storage task and contributes the highest reversible capacity and average discharge voltage. The disordered rock salt structure can reduce the long-range order of cations, thereby enabling the material to have a higher capacity. The spinel structure provides a low-barrier three-dimensional lithium-ion diffusion channel due to its inherent O-TM tetrahedra, which is beneficial to improving its rate performance. In addition, the spinel structure can partially ensure the relative stability of the structure.
[0009] 2. The disordered rock salt-spinel lithium manganese oxide core matrix of the present invention is prepared by a two-stage solid-state sintering method. In the first stage of high-temperature sintering, ordered spinel lithium manganese oxide is prepared. Subsequently, the ordered spinel lithium manganese oxide is sintered at an even higher temperature in the second stage. Because the atomic kinetic energy is extremely high at high temperatures, it is sufficient to overcome the energy barrier of the ordered arrangement, allowing Li... + and Fe 3+Initially, random exchanges of positions within the crystal lattice form a high-temperature disordered phase. The sample is then rapidly removed at high temperature and quenched, resulting in a disordered rock salt structure that retains a metastable state at room temperature. The purpose of quenching is to maintain the disordered atomic configuration at high temperatures. Furthermore, doping with heterovalent elements of different valence states or ionic radii exacerbates lattice distortion and local charge imbalance, effectively suppressing the driving force of long-range ordering by cations. This allows the disordered rock salt phase to remain stable over a wider temperature range, yielding a disordered rock salt phase with better crystallinity.
[0010] 3. The intermediate transition layer of the composite cathode material of the present invention is spinel-structured lithium manganese oxide. Due to its similar crystal structure to the core matrix and a lattice mismatch of less than 2%, it can achieve epitaxial growth to form a low-stress interface. During heat treatment, the Mn element in the transition layer interdiffusions with the Fe and P elements in the outer shell to form an extremely thin "gradient interface layer" with gradually changing chemical composition. This transition region can effectively relax the lattice mismatch stress caused by the difference in lattice constants and structural symmetry between the two materials, enhance the interfacial bonding force, and promote the transport of lithium ions between the interfaces.
[0011] 4. The outer shell of the composite cathode material of the present invention is a lithium iron phosphate material rich in lithium, which has the following functions: (1) physical barrier: isolates the core matrix from direct contact with the electrolyte, inhibits the dissolution of transition metals, release of lattice oxygen and the resulting continuous decomposition of electrolyte and increase of interface impedance; (2) inhibits core structure degradation: slows down the structural distortion and phase transition of the core matrix, thereby effectively inhibiting voltage decay and capacity decay during cycling. By introducing additional lithium elements into the lithium iron phosphate structure, lithium iron phosphate rich in lithium can effectively compensate for the loss of active lithium during the first charge and discharge process of lithium-ion batteries, and improve the energy density and cycle life of batteries. In addition, ion doping of lithium iron phosphate rich in lithium can further optimize its ionic conductivity, reduce the obstruction of the shell layer to lithium ion transport, and improve rate performance.
[0012] 5. In the composite cathode material of this invention, the disordered rock salt spinel manganese oxide core acts as an "energy engine," providing high capacity and high voltage, and is the main source of energy density. Furthermore, the disordered rock salt spinel manganese oxide core also exhibits high rate capability; the lithium iron phosphate shell acts as a "protective armor," providing ample protection to the surface structure of the core matrix material, thereby extending the cycle life of the composite cathode material under charged conditions; thanks to multiphase synergy, this composite material possesses high energy density, high rate capability, and excellent cycle performance.
[0013] 6. The composite cathode material of the present invention uses cobalt-free and nickel-free raw materials, thereby reducing material costs and dependence on scarce metals.
[0014] 7. This invention provides a method for preparing composite cathode materials. Through ingenious composition design, precipitation coating and transition layer construction, the lattice matching problem between traditional rock salt structure and polyanion structure can be effectively overcome, realizing the fusion of the two structures and giving full play to their respective advantages. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the core-shell structure of the composite cathode material of the present invention.
[0016] Figure 2 This is a transmission electron microscope (TEM) image of the composite cathode material in Embodiment 2 of the present invention. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0018] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0019] It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.
[0020] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0021] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product of this invention is in use, or the orientation or positional relationship commonly understood by those skilled in the art. They are only used for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention. In addition, the terms "first," "second," etc., are only used to distinguish descriptions and should not be construed as indicating or implying relative importance.
[0022] Example 1: A method for preparing a composite cathode material, comprising the following steps: Step 1: According to the chemical formula Li 1.2 Mn 0.6 Nb 0.2 Lithium carbonate, manganese trioxide, and niobium pentoxide were weighed out according to the stoichiometric ratio of O2 and placed in a ball mill jar. A measured amount of anhydrous ethanol was added, and the mixture was stirred at 450 rpm for 8 hours. The mixed first precursor material was placed in an oven and dried at 80°C for 12 hours. The dried material was pressed into thin sheets at 20 MPa and sintered in two stages. First, the temperature was raised to 850°C at a rate of 10°C / min and sintered for 10 hours; then, the temperature was raised to 1200°C at a rate of 3°C / min and sintered for 8 hours. The sintered material was quickly removed from the high-temperature furnace and immersed in liquid nitrogen for refining to obtain the first material. Step 2: Disperse the first material obtained in Step 1 in anhydrous ethanol, add lithium acetate and manganese acetate (Li:Mn=1:2), and stir and evaporate at 60°C to coat the core matrix with lithium manganese oxide precursor. After drying at 80°C, sinter at 650°C for 6 hours in an oxygen atmosphere to form an intermediate product with a LiMn2O4 transition layer. Step 3: Disperse the intermediate product obtained in Step 2 in anhydrous ethanol to obtain solution A. According to the stated chemical formula Li... 1.2 Fe 0.95 Ti 0.05 Ferric oxide, lithium dihydrogen phosphate, lithium carbonate, titanium dioxide, and glucose were weighed out according to the stoichiometric ratio of PO4. A measured amount of anhydrous ethanol and ethylene glycol were added, and the mixture was stirred at 550 rpm for 8 hours to obtain solution B. Solution B was then added dropwise to solution A at a rate of 10 ml / min under ultrasonic frequency of 150 kHz and stirring speed of 300 rpm. During this process, the solution temperature was maintained at 65℃, allowing solution B to uniformly nucleate and precipitate on the surface of the core matrix, resulting in a slurry. The slurry was dried at 80℃ for 12 hours. The dried second precursor was pressed into a thin sheet at 20 MPa and sintered at 750℃ for 10 hours to obtain the composite cathode material F0.
[0023] Example 2: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0024] Step 1 uses the chemical formula Li 1.2 Mn 0.625 Nb 0.175 O 1.95 F 0.05 The raw materials were weighed according to the stoichiometric ratio, with lithium fluoride used as the F source, and the final composite material F1 was obtained.
[0025] Example 3: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0026] Step 1 uses the chemical formula Li 1.2 Mn 0.65 Nb 0.15 O 1.9 F 0.1 The raw materials were weighed according to the stoichiometric ratio, and the final composite material F3 was obtained.
[0027] Example 4: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0028] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Nb 0.1 O 1.8 F 0.2 The raw materials were weighed according to the stoichiometric ratio, and the final composite material F4 was obtained.
[0029] Example 5: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0030] Step 3, the outer shell material is coated according to Li 1.0 Fe 0.95 Mg 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F5.
[0031] Example 6: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0032] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Mg 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Ti 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F6.
[0033] Example 7: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0034] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Ta 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Zr 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F7.
[0035] Example 8: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0036] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Mo 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Al 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F8.
[0037] Example 9: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0038] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Fe 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Mn 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F9.
[0039] Example 10: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0040] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Zr 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Ni 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F10.
[0041] Example 11: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0042] Step 1 uses the chemical formula Li 1.2 Mn 0.7 W 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0Fe 0.95 Zn 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F11.
[0043] Example 12: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0044] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Ti 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Co 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain the composite material F12.
[0045] Example 13: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0046] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Ti 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Cu 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F13.
[0047] Example 14: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0048] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Ti 0.1 O 1.9 F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 Cr 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain the composite material F14.
[0049] Example 15: A method for preparing a composite cathode material, which differs from Example 1 in that:
[0050] Step 1 uses the chemical formula Li 1.2 Mn 0.7 Ti 0.1 O 1.9F 0.1 The raw materials are weighed according to the stoichiometric ratio. Step two is the same as in Example 1. However, in step three, the outer shell material is coated according to Li... 1.0 Fe 0.95 V 0.05 The raw materials were weighed according to the stoichiometric ratio of PO4 to obtain composite material F15.
[0051] Comparative Example 1 A method for preparing a composite cathode material, wherein the material obtained after preparation according to step one of Example 1 is used as the cathode material of the battery.
[0052] Comparative Example 2 According to the general chemical formula Li 1.2 Fe 0.95 Ti 0.05 Ferric oxide, lithium dihydrogen phosphate, lithium carbonate, titanium dioxide, and glucose were weighed out according to the stoichiometric ratio of PO4. A measured amount of anhydrous ethanol and ethylene glycol were added, and the mixture was stirred at 550 rpm for 8 hours to obtain a slurry. The slurry was then dried at 80°C for 12 hours. The dried material was pressed into thin sheets at 20 MPa and sintered at 750°C for 10 hours to obtain a lithium-rich lithium iron phosphate cathode material.
[0053] Example 16: Battery Performance Test The cathode materials of Examples 1-15 and Comparative Examples 1-2 were used to prepare batteries for electrical performance testing. The test results are shown in Table 1.
[0054] Table 1. Results of electrical performance tests on batteries prepared from the cathode materials of Examples 1-15 and Comparative Examples 1-2. Example 1 259 89.2 86.7 Example 2 260 90.5 91.2 Example 3 231 90.2 92.1 Example 4 197 89.5 93.5 Example 5 183 89.9 87.2 Example 6 188 89.7 88.6 Example 7 185 90.2 86.7 Example 8 178 91.3 89.1 Example 9 182 90.9 85.4 Example 10 187 90.5 87.9 Example 11 188 89.9 85.6 Example 12 190 91.5 88.9 Example 13 189 90.8 88.8 Example 14 191 90.1 85.7 Example 15 187 87.6 85.6 Comparative Example 1 269 78.3 61.5 Comparative Example 2 161 93.5 98.2 As shown in Table 1 above, the composite cathode material of the present invention, through the coating of lithium-rich lithium iron phosphate, provides sufficient protection to the surface structure of the core matrix material, thereby extending the cycle life of the composite cathode material under charged state, and improving the capacity retention rate of the battery after 500 cycles at 1C by approximately 30%. Compared with lithium iron phosphate, the composite cathode material of the present invention benefits from multiphase synergy, and the composite material has high capacity, high rate performance, and excellent cycle performance.
[0055] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite cathode material, characterized in that: The composite cathode material has a core-shell structure; the core-shell structure includes, from the inside out, a core matrix, a transition layer, and an outer shell; the core matrix is disordered rock salt-spinel lithium manganese oxide; the transition layer is lithium manganese oxide; and the outer shell is lithium iron phosphate rich in lithium. The general chemical formula of the disordered rock salt-spinel lithium manganese oxide core matrix is: Li 1+b Mn 0.8-y N y O 2-y F n Where 0.1 < b ≤ 0.3, 0.1 < y ≤ 0.5, 0.05 < n ≤ 0.2; N is Mg 2+ Fe 3+ Ti 4+ Zr 4+ 、Nb 5+ Mo 6+ Ta 5+ W 6+ One or more of the following; The transition layer lithium manganese oxide has a spinel structure and its chemical formula is: LiMn2O4; The general chemical formula of the lithium iron phosphate shell is: Li 1+a Fe 1-x M x PO4; where 0 < a ≤ 0.2, 0 ≤ x ≤ 0.2; M is Mg 2+ Ti 4+ Zr 4+ Mn 2+ Zn 2+ Cu 2+ Al 3+ V 3+ Cr 3+ Co 2+ Ni 2+ One or more of the following; The thickness of the transition layer is 5nm to 50nm; the thickness of the outer shell is 10nm to 100nm.
2. The composite cathode material according to claim 1, characterized in that: The particle size of the core matrix is 200nm to 500nm.
3. A method for preparing a composite cathode material, characterized in that: The method for preparing the composite cathode material according to any one of claims 1-2 comprises the following steps: Step 1: Preparation of the core matrix: According to the stated chemical formula Li 1+b Mn 0.8-y N y O 2-y F n Manganese source, lithium source, N metal source and lithium fluoride were weighed according to the stoichiometric ratio, dissolved in solvent, ball-milled and mixed evenly, and dried to obtain the first precursor powder; the first precursor powder was pressed into tablets and sintered in two stages under a protective atmosphere; the sintered material was quickly taken out from the high-temperature furnace and put into the cooling medium, and after refinement, the disordered rock salt spinel lithium manganese oxide core matrix was obtained. Step 2: Constructing the transition layer: The disordered rock salt-spinel lithium manganese oxide core matrix obtained in Step 1 is dispersed in a solvent, and lithium acetate and manganese acetate are added, wherein the lithium-manganese molar ratio is Li:Mn = (1.0~1.10): 2; stirring and evaporation are carried out to coat the disordered rock salt-spinel lithium manganese oxide core matrix with the lithium manganese oxide precursor; after drying, it is sintered in an oxygen atmosphere to form an intermediate product with a lithium manganese oxide transition layer; Step 3: Preparation of composite cathode material: The intermediate product obtained in Step 2 is dispersed in a solvent to obtain solution A; according to the stated chemical formula Li 1+a Fe 1-x M x Iron, phosphorus, lithium, M metal, and carbon sources were weighed out in stoichiometric proportions for PO4, and solvent and dispersant were added. The mixture was ball-milled to obtain solution B. Under the combined action of stirring and sonication, solution B was slowly added dropwise to solution A. The mixture was stirred and evaporated, so that solution B was uniformly nucleated and precipitated on the surface of the intermediate product to obtain a slurry. The slurry was dried to obtain a second precursor powder, which was then pressed into tablets, sintered under a protective atmosphere, and pulverized by airflow to obtain a composite cathode material.
4. The method for preparing the composite cathode material according to claim 3, characterized in that: In step one, the manganese source is selected from one or more of manganese dioxide, manganese nitrate, and manganese chloride; the lithium source is selected from one or more of lithium hydroxide, lithium nitrate, and lithium carbonate; in step three, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium acetate; the iron source is selected from one or more of ferrous oxalate, ferric phosphate, and ferrous chloride; the phosphorus source is selected from one or two of ammonium dihydrogen phosphate or lithium dihydrogen phosphate; in step three, the carbon source is selected from one or a combination of two of glucose, sucrose, citric acid, ascorbic acid, tartaric acid, polyethylene glycol, polyvinyl butyral, polyvinyl alcohol, and starch, and the carbon source content accounts for 3-15 wt% of the total solids; in step three, the dispersant is selected from one of polyethylene glycol, ethylene glycol, polyacrylic acid, and stearic acid; in steps one and three, the protective atmosphere during sintering is one of nitrogen, argon, and helium; the solvent used in steps one, two, and three is anhydrous ethanol.
5. The method for preparing the composite cathode material according to claim 3, characterized in that: Step one, specifically the two-stage sintering process, includes the following steps: The first stage adopts low-temperature sintering: heating rate 5℃ / min~15℃ / min; sintering temperature 800℃~1000℃; sintering time 8h~12h. The second stage employs high-temperature sintering: the heating rate is 2℃ / min~5℃ / min; the sintering temperature is 1100℃~1300℃; and the sintering time is 8h~12h. In step one, the cooling medium used after the two sintering stages is liquid nitrogen or ice water.
6. The method for preparing the composite cathode material according to claim 3, characterized in that: In step one, the ball mill speed is 300 rpm to 500 rpm; the ball milling time is 5 h to 8 h; in step three, the ball mill speed is 600 rpm to 800 rpm; the ball milling time is 2 h to 5 h.
7. The method for preparing the composite cathode material according to claim 3, characterized in that: In step three, the ultrasonic frequency is 120 kHz to 180 kHz; the stirring speed is 200 rpm to 400 rpm; the solution dropping rate is 5 ml / min to 50 ml / min; in step three, the heating rate during sintering is 2℃ / min to 5℃ / min, the sintering temperature is 600℃ to 850℃, and the sintering time is 8h to 12h.
8. The method for preparing the composite cathode material according to claim 3, characterized in that: In steps one, two, and three, the drying temperature is 75℃~120℃, and the drying time is 6h~12h; in steps one and three, the drying powder is pressed into flakes under conditions of 15 MPa~25 MPa; in steps two and three, the solution is stirred and evaporated at a temperature of 45℃~80℃.
9. A lithium-ion battery, characterized in that, include: A positive current collector, a negative current collector, a separator, and an electrolyte solution; wherein the positive current collector is coated with a positive electrode layer; the positive electrode layer comprises a positive electrode material; the positive electrode material is the composite positive electrode material according to any one of claims 1-2.
Citation Information
Patent Citations
Core-shell composite anode material for lithium ion battery and preparation method thereof
CN101740752A
Composite positive electrode material, preparation method thereof and lithium ion battery
CN111952560A